Species richness and longitudinal distribution of crustaceans in the Logawa River, Banyumas, Indonesia - Moh. Husein Sastranegara; KUSBIYANTO KUSBIYANTO; ANASTASIA ENDANG PULUNGSARI (Society for Indonesian Biodiversity, 2020)
Abstract. Sastranegara MH, Kusbiyanto, Pulungsari AE. 2020. Species richness and longitudinal distribution of crustaceans in the Logawa River, Banyumas, Indonesia. Biodiversitas 21: 5322-5330. The Logawa River originates in a forest on Slamet Mountain and empties into the Serayu River. In this river, crustaceans play an important role as river macrobenthos. This research aimed to evaluate the species richness and longitudinal distribution of crustaceans. The research method was a stratified random sampling technique at eight stations with five replicates. Crustacean samples were collected using a Surber net, and water samples were taken with a water sampler. The results showed that there were six species of Decapoda in the river. Of these six species, three were shrimps and three were crabs. In longitudinal distribution, the shrimp Macrobrachium idae could be categorized as a cosmopolitan species that inhabited all stations, although there were several river branches before Stations IV (Cangkring Stream), V (Mengaji Stream), and VI (Banjaran Stream), bedrock substrate at Station I, high ammonia at all stations and high chemical oxygen demand (COD) between Stations IV and VIII. The crab Varuna litterata was found only at Station VI. In general, the species richness decreased after Station IV due to COD from the riverside. This was caused by human activities such as stone and sand excavation and overfishing in the habitat. The upstream habitat with its bedrock substrate was not suitable for decapods, except for cosmopolitan species.